Energy saving behavior in university organizations: The value of norm constructions in a “rational choice” action model - Heib, Sascha; Hildebrand, Jan; Kortsch, Timo (Frontiers in Psychology, 2023)
In times of rising energy prices and increasing importance of climate change, saving energy becomes even more important. Universities are large public institutions with significant energy-saving potential. This study investigated the energy-saving behavior of students and employees at a German university. In contrast to previous studies, which often focused on individual buildings, this study took a comprehensive approach and addressed all university members (employees and students). A extended model of the Theory of Planned Behavior (TPB) served as the theoretical basis. Considering the specific organizational context, the main question of the study was to explore the interlinkages between the intention to save energy, corresponding consumption behavior, and the effects of injunctive and descriptive social norms within the social system of the organization. Furthermore, the impact of “not energy related” factors like the identification with the organization was tested. As methodological approach a university-wide quantitative online survey was conducted. For the survey, a standardized questionnaire containing several scales on energy consumption behavior and TBP-constructs was used. All in all, data from a total of 1,714 members of the university participating in the study was analyzed. Structural equation modeling showed that the extended TPB model yields a satisfactory amount of explained variance (approximately 40%) for intention and a moderate amount (approximately 20%) for behavior. The strongest predictors are personal norm and behavioral control. The organizational influence factor identification was also significant for intention, but only to a small extent. The results extend the understanding of the theory of planned behavior in the context of energy conservation in universities and emphasize that the sense of behavioral control and the personal norm must always be considered when intervening in this context to promote energy conservation and thus provide valuable hints for practical measures.